PARTISIPASI ORGANISASI HIMPUNAN WANITA DISABILITAS INDONESIA (HWDI) DALAM PEMENUHAN PERLINDUNGAN HAK DISABILITAS DARI BENCANA COVID-19 di DKI JAKARTA - Salsabila, Widyadhari (2021)
This study aims to examine the mitigation process of groups of persons with disabilities, namely the Indonesian Association of Women with Disabilities (HWDI) in fighting for the protection of the rights of vulnerability from the Covid -19 disaster in DKI Jakarta using a citizenship perspective. Participation in the perspective of citizenship forces citizens to actively encourage the government to fulfill the rights they have postponed. Researchers use the political theoretical framework of Stokke citizenship and Young's concept of inclusive citizenship to examine how far forms of HWDI participation can influence the Provincial Government of DKI Jakarta in fulfilling the right to protection of vulnerability from disasters. Researchers used a qualitative descriptive method with data analysis using narrative techniques. The results of the study show that the form of participation carried out by the HWDI organization has been able to influence the DKI Jakarta provincial government with the positive response shown by the Jakarta Provincial Government regarding the Jakarta HWDI participation activities. As for the dimension of citizenship as a right, what has not been fulfilled is the social, civil and political rights of disability which has a negative implication that the handling of the Covid-19 disaster is not yet inclusive. Keywords: Persons with disabilities, citizenship politics, disability protection rights from disasters.